Association between multimorbidity and mortality in a cohort of patients admitted to hospital with COVID-19 in Scotland. (January 2022) - Agrawal, Utkarsh; Azcoaga-Lorenzo, Amaya; Fagbamigbe, Adeniyi Francis; Vasileiou, Eleftheria; Henery, Paul; Simpson, Colin R; Stock, Sarah J; Shah, Syed Ahmar; Robertson, Chris; Woolhouse, Mark; Ritchie, Lewis D; Shiekh, Aziz; et al.
Objectives: We investigated the association between multimorbidity among patients hospitalised with COVID-19 and their subsequent risk of mortality. We also explored the interaction between the presence of multimorbidity and the requirement for an individual to shield due to the presence of specific conditions and its association with mortality. Design: We created a cohort of patients hospitalised in Scotland due to COVID-19 during the first wave (between 28 February 2020 and 22 September 2020) of the pandemic. We identified the level of multimorbidity for the patient on admission and used logistic regression to analyse the association between multimorbidity and risk of mortality among patients hospitalised with COVID-19. Setting: Scotland, UK. Participants: Patients hospitalised due to COVID-19. Main outcome measures: Mortality as recorded on National Records of Scotland death certificate and being coded for COVID-19 on the death certificate or death within 28 days of a positive COVID-19 test. Results: Almost 58% of patients admitted to the hospital due to COVID-19 had multimorbidity. Adjusting for confounding factors of age, sex, social class and presence in the shielding group, multimorbidity was significantly associated with mortality (adjusted odds ratio 1.48, 95%CI 1.26–1.75). The presence of multimorbidity and presence in the shielding patients list were independently associated with mortality but there was no multiplicative effect of having both (adjusted odds ratio 0.91, 95%CI 0.64–1.29). Conclusions: Multimorbidity is an independent risk factor of mortality among individuals who were hospitalised due to COVID-19. Individuals with multimorbidity could be prioritised when making preventive policies, for example, by expanding shielding advice to this group and prioritising them for vaccination.